Electrolyte for preparing micro-arc oxidation ceramic film of high-hardness corrosion-resistant aluminum-lithium alloy and preparation method thereof
Patent Information
- Application Number
- CN202611016055.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-09
AI Technical Summary
Aluminum-lithium alloys have low surface hardness, poor wear resistance, and high corrosion sensitivity, which limits their application in complex and extreme environments.
By optimizing the micro-arc oxidation process parameters of aluminum-lithium alloys and adding KF, K2ZrO3, KH2PO4 and NaOH to the electrolyte to promote the formation of α-Al2O3 and reduce Li2O, a high-hardness and high-density composite ceramic film is formed by using plasma powder spraying and secondary micro-arc oxidation processes.
It significantly improves the hardness and corrosion resistance of aluminum-lithium alloy micro-arc oxidation film, increasing hardness by more than 30% and corrosion resistance by more than 40%, meeting the requirements for use in harsh environments.
Smart Images

Figure CN122522357B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of aluminum-lithium alloy surface treatment technology and micro-arc oxidation technology, specifically relating to a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film electrolyte and its preparation method. Background Technology
[0002] Aluminum-lithium alloy is a new type of low-density, high-performance aluminum alloy material, with lithium as its key alloying element. By rationally adding lithium and other elements and employing advanced processing techniques, the synergistic effects of each element can be fully utilized to obtain an alloy material with excellent comprehensive performance. Aluminum-lithium alloy has the following characteristics: 1) Low density: Lithium has a low density, and adding it to aluminum effectively reduces the alloy density. Compared to traditional aluminum alloys, the density of aluminum-lithium alloy can be reduced by about 10-15%, which is beneficial for achieving lightweight components. 2) High specific strength and specific stiffness: While reducing density, aluminum-lithium alloy maintains high strength and stiffness, with significantly improved specific strength and specific stiffness compared to ordinary aluminum alloys, allowing it to withstand greater loads. 3) Good fatigue resistance: After appropriate processing and heat treatment, aluminum-lithium alloy exhibits good fatigue resistance, able to withstand more stress cycles under cyclic loading without fatigue failure. 4) Excellent low-temperature performance: In low-temperature environments, aluminum-lithium alloy still maintains good mechanical properties; its strength and toughness do not decrease significantly, making it suitable for low-temperature working environments. Aluminum-lithium alloys have a wide range of applications, primarily in: 1) Aerospace: used to manufacture aircraft wings, fuselage structural components, landing gear, etc., reducing aircraft weight, improving fuel efficiency, and increasing range and payload. 2) Weaponry: used to manufacture weapon components, such as missile bodies and tank armor, reducing equipment weight and improving mobility and combat effectiveness. 3) Electronics: used to manufacture the casings and frames of electronic devices, reducing weight while ensuring structural strength and electromagnetic shielding performance. 4) Automotive: used to manufacture automotive engine blocks, body frames, and other components, contributing to vehicle lightweighting and reducing fuel consumption and emissions.
[0003] Although aluminum-lithium alloys have become core lightweight structural materials in aerospace and high-end equipment fields due to their excellent characteristics of low density and high specific strength, their application range has always been limited by two core performance shortcomings: first, low surface hardness and poor wear resistance; second, prominent corrosion sensitivity. Multiple factors together determine their application limitations in complex and extreme environments.
[0004] From the perspective of inherent material properties, the root cause of corrosion sensitivity lies in the intrinsic chemical characteristics of lithium: lithium ranks high in the metal activity series, is extremely chemically reactive, and its standard electrode potential is much lower than that of alloying elements in conventional aluminum alloys. At the same time, aluminum-lithium alloys themselves have low surface hardness and insufficient wear resistance, making them extremely susceptible to damage to surface integrity due to friction and wear during service, directly losing the basis of surface protection.
[0005] In natural service environments, this inherent characteristic quickly translates into actual corrosion behavior. Especially in high-humidity atmospheres, chloride-ion-containing marine environments, or industrial corrosion environments with electrolytes, lithium atoms in the alloy preferentially diffuse from the aluminum matrix to the surface, readily reacting with oxygen and moisture in the air to generate corrosion products such as lithium oxide and lithium hydroxide. These products are much larger than the lithium atoms involved in the reaction, generating significant expansion stress on the alloy surface. This stress directly breaks through the aluminum oxide passivation film that originally provided protection. Without the protection of the passivation film, the internal aluminum matrix and unreacted lithium elements are directly exposed to the corrosive medium, triggering a continuous electrochemical reaction and forming a vicious cycle of "surface film rupture - internal metal exposure - accelerated corrosion reaction - further film damage".
[0006] In addition to the inherent activity of lithium itself, the microscopic defects formed in aluminum-lithium alloys during the entire process of ingot solidification and plastic processing further amplify the corrosion effect, creating a significant superposition effect with surface corrosion. Grain boundary segregation: During solidification, the solute redistribution coefficient of lithium is much less than 1, resulting in a large accumulation of lithium in the last solidified grain boundaries and triangular grain boundaries, causing severe compositional inhomogeneity between the grain boundaries and the interior of the grains. This difference weakens the mechanical bonding strength of the grain boundaries and forms natural electrical couples in the corrosive environment: the lithium-rich grain boundary regions have lower electrode potentials and preferentially dissolve as anodes, causing corrosion to rapidly extend along the grain boundaries into the interior of the alloy, inducing highly destructive intergranular corrosion.
[0007] Shrinkage cavities (including micro-shrinkage porosity): During the cooling and solidification of liquid aluminum-lithium alloys, significant volume shrinkage occurs. If the melt feeding is insufficient, shrinkage cavities ranging from micrometers to millimeters will form at grain boundaries and between dendrites. Large, concentrated cavities are called shrinkage cavities, while small, dispersed cavities are called micro-shrinkage porosity. These three-dimensional pores become "intrusion and storage channels" for corrosive media. Even if a passivation film reforms on the alloy surface, the closed environment inside the pores will maintain continuous corrosion. Furthermore, the localized acidification effect within the pores will further accelerate the corrosion rate. Simultaneously, stress concentration at the pore edges will couple corrosion with mechanical damage, significantly increasing the risk of stress corrosion cracking.
[0008] All microscopic defects also share a common corrosion-accelerating effect: the irregular atomic arrangement and higher system energy at the defect location naturally become active sites for corrosion reactions in corrosive media, leading to preferential corrosion; at the same time, the uneven distribution of lithium in the alloy means that lithium-rich areas themselves become preferential initiation zones for corrosion, further exacerbating the development of localized corrosion.
[0009] In actual engineering service, there are additional corrosion risks: aluminum-lithium alloys often need to be used in conjunction with other metal materials such as titanium alloys and high-strength steel. Due to the significant difference between the electrode potential of aluminum-lithium alloys and these metals, galvanic couples will be formed in the electrolyte environment, triggering the galvanic corrosion effect: aluminum-lithium alloys with lower potential will act as the anode and be preferentially corroded, further accelerating material failure.
[0010] The combined effects of intrinsic lithium activity, microstructural defects, and service environment ultimately lead to a significantly higher corrosion rate for lithium-aluminum alloys compared to conventional aluminum alloys, directly limiting their large-scale application in harsh environments.
[0011] Micro-arc oxidation technology is developed based on anodic oxidation. The metal workpiece is placed in an electrolyte, and under high voltage and high current, the oxide film on the metal surface breaks down, generating a micro-area arc discharge. The instantaneous high temperature and pressure cause a chemical reaction between the metal on the metal surface and the oxygen in the electrolyte, resulting in the in-situ growth of a ceramic film on the metal surface. The characteristics of micro-arc oxidation technology are as follows: 1) High hardness and wear resistance: The generated ceramic film has high hardness, significantly improving the wear resistance of the metal surface and effectively resisting friction and wear. 2) Good corrosion resistance: The ceramic film has good chemical stability and density, preventing corrosive media from contacting the metal substrate and improving corrosion resistance. 3) Good insulation performance: An insulating layer can be formed on the metal surface, meeting some electrical insulation requirements. Therefore, micro-arc oxidation technology can solve the problems of low surface hardness and poor wear resistance of aluminum-lithium alloys, as well as the galvanic corrosion effect that often occurs when aluminum-lithium alloys are used in combination with other metal materials. However, the micro-arc oxidation film prepared on the surface of aluminum-lithium alloys by traditional micro-arc oxidation processes is mainly γ-Al2O3 with α-Al2O3 as a secondary component. γ-Al₂O₃ has high activity and specific surface area, which helps improve the adhesion between the film and the substrate, but its low hardness leads to relatively poor wear resistance. α-Al₂O₃, on the other hand, has high hardness and good chemical stability, giving the film excellent wear and corrosion resistance. During the micro-arc oxidation process, aluminum-lithium alloys produce a small amount of Li₂O, which alters the electrical properties of the film, such as conductivity and dielectric constant, reducing its insulation and corrosion resistance. Furthermore, the presence of Li₂O results in poor microstructure density, causing the film's hardness and wear resistance to fail to meet the requirements for use in harsh environments. Summary of the Invention
[0012] To address the aforementioned technical problems, this invention provides a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film electrolyte and its preparation method. By optimizing the micro-arc oxidation process parameters of aluminum-lithium alloy and adding specific additives to the electrolyte, it helps to increase the content of α-Al2O3 and the density of the aluminum-lithium alloy micro-arc oxidation film, improve the film hardness, and reduce the presence of Li2O in the film, thereby further improving the hardness and corrosion resistance of the aluminum-lithium alloy.
[0013] This invention is achieved by providing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic membrane electrolyte, comprising the following components: Na2SiO3 15-20g / L, KH2PO4 3-5g / L, NaOH 1-3g / L, KF 1-3g / L, and K2ZrO3 2-4g / L.
[0014] The components in the electrolyte have a synergistic modifying effect: KF can react chemically with the Li2O generated in the film layer, converting the alkaline and unstable Li2O into chemically stable inert LiF, thus completely eliminating film defects and electrochemical corrosion hazards caused by lithium enrichment; K2ZrO3 can generate a high-hardness ZrO2 hard phase in situ in the film layer, significantly improving the overall hardness and wear resistance of the film layer; KH2PO4 and NaOH work synergistically to promote film densification and increase the amount of ceramic phase generated.
[0015] A method for preparing the high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic membrane electrolyte is provided. First, 2-4 g / L of K2ZrO3 is dissolved in pure water, and then 15-20 g / L of Na2SiO3, 3-5 g / L of KH2PO4, 1-3 g / L of NaOH, and 1-3 g / L of KF are added sequentially. After thorough stirring, a composite electrolyte is obtained.
[0016] A method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film is provided, comprising the following steps: S1) Sample pretreatment: The aluminum-lithium alloy sample is subjected to mechanical grinding, degreasing, alkaline washing and acid washing in sequence to remove oxide scale, processing marks, oil stains and free lithium ions on the sample surface and activate the alloy substrate surface. S2) Preparation of micro-arc oxidation electrolyte: Prepared based on the above-mentioned preparation method of high-hardness corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic membrane electrolyte; S3) First micro-arc oxidation treatment: The pretreated aluminum-lithium alloy sample is placed in the electrolyte, and the micro-arc oxidation reaction is carried out in the mode of first applying positive current and then applying positive and negative current simultaneously. The temperature is controlled throughout the process to complete the initial growth of ceramic film. S4) Surface spraying treatment: After cleaning and drying the sample after one micro-arc oxidation, a zirconium oxide layer is uniformly sprayed onto the surface of the film using a plasma powder spraying process. S5) Secondary micro-arc oxidation treatment: The sample after being sprayed with zirconium oxide is placed again in the electrolyte prepared in step 2), and secondary micro-arc oxidation is performed using a positive and negative energizing mode. The loose zirconium oxide on the surface is wrapped inside the ceramic film layer, and a high-density, high-hardness, and highly corrosion-resistant composite ceramic film layer is generated in situ.
[0017] Preferably, in step S1), the mechanical polishing is performed by using sandpaper of different grits, polishing from coarse to fine, and finally using #1000 sandpaper for fine polishing; the degreasing is performed by using an alkaline degreasing agent and soaking at 50°C for 15 minutes; the alkaline washing is performed by using a 5% NaOH solution and treating at 60°C for 5 minutes to remove the natural oxide film on the alloy surface; the acid washing is performed by using a 20% HNO3 solution and soaking at room temperature for 3 minutes to neutralize alkaline residue, remove free lithium ions on the surface, and activate the substrate surface.
[0018] Preferably, in step S3), the process parameters for the first micro-arc oxidation are: positive voltage 500V, negative voltage 100V, frequency 700Hz, positive / negative duty cycle 40 / 30, and oxidation time 4h. During the micro-arc oxidation process, the electrolyte temperature is kept constant at 40±2℃ by a circulating cooling system. The mode of first applying positive current and then applying positive and negative current simultaneously can effectively improve the film density and reduce microscopic defects.
[0019] Preferably, in step S5), the process parameters for the secondary micro-arc oxidation are: positive voltage 510V, negative voltage 120V, frequency 700Hz, positive and negative duty cycle 40 / 30, and oxidation time 4h; the electrolyte temperature is constantly controlled at 40±2℃ during the secondary micro-arc oxidation process.
[0020] The parameters of primary and secondary micro-arc oxidation are synergistically matched to effectively regulate the phase composition of the film, significantly increase the proportion of high-hardness, high-stability α-Al2O3 hard ceramic phase in the film, reduce the content of low-hardness, high-activity γ-Al2O3, further optimize the density and uniformity of the film, and eliminate micropores and crack defects.
[0021] Preferably, the thickness of the aluminum-lithium alloy micro-arc oxidation ceramic film is 40-45 μm.
[0022] Preferably, the aluminum-lithium alloy micro-arc oxidation ceramic film has an average hardness of not less than 1820 HV and a neutral salt spray tolerance time of 1900 h. Compared with traditional micro-arc oxidation film layers, the hardness is increased by more than 30% and the corrosion resistance is increased by more than 40%.
[0023] Preferably, the aluminum-lithium alloy is a 2195 grade aluminum-lithium alloy.
[0024] Compared with the prior art, the advantages of the present invention are as follows: 1) Through the pretreatment steps of the present invention, impurities and oxide films on the surface of aluminum-lithium alloys can be effectively removed, while the lithium ion content on the sample surface can be effectively reduced, which is beneficial to the growth of micro-arc oxide film and the improvement of hardness and corrosion resistance. 2) Adding KF to the electrolyte converts Li2O generated in the film into LiF, thereby further improving the corrosion resistance of the film. Adding K2ZrO3 introduces a small amount of ZrO2 into the film, further increasing its hardness. Adding KH2PO4 and NaOH promotes densification of the micro-arc oxidation film, increasing the content of the ceramic phase and thus improving its hardness. Furthermore, through the combined effect of KH2PO4 and NaOH in the solution, along with the optimized negative electrode application process and adjustment of electrical parameters in micro-arc oxidation, more α-Al2O3 can be generated during the micro-arc oxidation process, reducing the content of γ-Al2O3 in the film, thereby further improving the hardness of the micro-arc oxidation film. The resulting micro-arc oxidation film exhibits good uniformity and fewer defects. Based on this, a zirconium oxide layer is sprayed onto the film surface using plasma powder spraying. After the zirconium oxide is uniformly attached to the film surface, a second micro-arc oxidation is performed. This encapsulates the relatively loose ZrO2 on the surface into the α-Al2O3 micro-arc oxidation film, significantly improving the surface hardness and corrosion resistance. 3) The composite ceramic film prepared by this method has an average hardness of not less than 1820 HV and a neutral salt spray tolerance time of up to 1900 hours. The hardness of the micro-arc oxidation film prepared by this invention is more than 30% higher than that of the film prepared by the traditional micro-arc oxidation process. The corrosion resistance is improved by more than 40% compared with the previous method. Attached Figure Description
[0025] Figure 1 The hardness of the aluminum-lithium alloy micro-arc oxidation film prepared in Example 1; Figure 2 This is a schematic diagram of the thickness of the aluminum-lithium alloy micro-arc oxidation film prepared in Example 1; Figure 3 The appearance of the aluminum-lithium alloy micro-arc oxidation film prepared in Example 1 after 1900 hours of neutral salt spray. Figure 4 The image shows the microstructure of the aluminum-lithium alloy micro-arc oxidation film prepared in Example 1. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.
[0027] Example 1
[0028] Step S1) Sample pretreatment: The aluminum-lithium alloy sample was treated sequentially as follows: ① Mechanical grinding: using #180→#400→#800→#1000 sandpaper to grind from coarse to fine, and finally using #1000 sandpaper for fine grinding to remove the oxide scale and processing marks on the surface; ② Degreasing: soaking in an alkaline degreasing agent at 50℃ for 15 minutes to remove oil stains; ③ Alkaline washing: treating with 5wt% NaOH solution at 60℃ for 5 minutes to remove the natural oxide film on the surface; ④ Acid washing: soaking in 20wt% HNO3 solution at room temperature for 3 minutes to neutralize alkaline residue, remove free lithium ions on the surface and activate the matrix; Step S2) Preparation of micro-arc oxidation electrolyte: First, dissolve 2 g / L K2ZrO3 in pure water, then add 15 g / L Na2SiO3, 3 g / L KH2PO4, 1 g / L NaOH, and 1 g / L KF in sequence, and stir thoroughly. Step S3) Setting of micro-arc oxidation process parameters: Use positive and negative power application mode, set the positive voltage to 500V and the negative voltage to 100V, the frequency to 700Hz, the positive and negative duty cycle to 40 / 30, and the oxidation time to 4h. During the micro-arc oxidation process, the electrolyte temperature is controlled at 40±2℃, which is achieved through a circulating cooling system. Step S4) Zirconia Plasma Powder Coating: After the sample is cleaned and dried after the first oxidation, a zirconia layer is uniformly sprayed onto the film surface using a plasma powder coating process. Step S5) Setting the parameters for the secondary micro-arc oxidation process: After spraying, the sample is returned to the original electrolyte. The positive and negative power-on mode is adopted. The positive voltage of the micro-arc oxidation is set to 510V, the negative voltage is set to 120V, the frequency is 700Hz, the positive and negative duty cycle is 40 / 30, and the oxidation time is 4h. During the micro-arc oxidation process, the electrolyte temperature is controlled at 40±2℃, which is achieved through a circulating cooling system.
[0029] Performance testing: After treatment, the hardness of the micro-arc oxidation film was tested at five sites. The maximum hardness was 1962.2 HV, the minimum was 1794.5 HV, and the average hardness was 1855.7 HV. Figure 1 As shown; thickness 40μm, as Figure 2 As shown; the salt spray time was 1900 hours, and the appearance of the film layer after the salt spray test was as follows. Figure 3 As shown; the film morphology is as follows Figure 4 As shown.
[0030] Example 2
[0031] Step S1) Sample pretreatment: completely consistent with Example 1; Step S2) Preparation of micro-arc oxidation electrolyte: First, dissolve 4 g / L K2ZrO3 in pure water, then add 20 g / L Na2SiO3, 5 g / L KH2PO4, 3 g / L NaOH and 3 g / L KF in sequence, and stir thoroughly. Step S3) Setting the micro-arc oxidation process parameters: completely consistent with the process parameters in Example 1; Step S4) Zirconia plasma powder coating: completely consistent with Example 1; Step S5) Setting the secondary micro-arc oxidation process parameters: completely consistent with the process parameters in Example 1; Performance testing: average hardness 1827.7 HV, film thickness 45 μm, neutral salt spray tolerance time 1900 h.
[0032] Example 3
[0033] Step S1) Sample pretreatment: completely consistent with Example 1; Step S2) Preparation of micro-arc oxidation electrolyte: First, dissolve 3 g / L K2ZrO3 in pure water, then add 17.5 g / L Na2SiO3, 4 g / L KH2PO4, 2 g / L NaOH, and 2 g / L KF in sequence, and stir thoroughly. Step S3) Setting the micro-arc oxidation process parameters: completely consistent with the process parameters in Example 1.
[0034] Step S4) Zirconia plasma powder coating: completely consistent with Example 1; Step S5) Setting the secondary micro-arc oxidation process parameters: completely consistent with the process parameters in Example 1; Performance testing: average hardness 1820.6 HV, film thickness 42 μm, neutral salt spray tolerance time 1900 h.
[0035] Comparative Example 1 Step S1) Sample pretreatment: completely consistent with Example 1; Step S2) Preparation of micro-arc oxidation electrolyte: only add 15g / L Na2SiO3, 3g / L KH2PO4, and 1g / L NaOH, without adding KF and K2ZrO3. The rest of the preparation order is the same, and stir thoroughly. Step S3) Micro-arc oxidation only: The process parameters are the same as in Example 1, without spraying and secondary oxidation steps.
[0036] Performance testing: film thickness 28μm, average hardness 662HV, neutral salt spray tolerance time 720h.
[0037] Comparative Example 2 Steps S1-S3): Completely the same as in Example 1, except that steps S4 (plasma spraying) and S5 (secondary micro-arc oxidation process) are omitted.
[0038] Performance testing: film thickness 32μm, average hardness 1535HV, neutral salt spray tolerance time 1200h.
[0039] Comparative Example 3 Step S1) Sample pretreatment: completely consistent with Example 1.
[0040] Step S2) Preparation of micro-arc oxidation electrolyte: Without pre-dissolving K2ZrO3, add 15g / L Na2SiO3, 3g / L KH2PO4, 1g / L NaOH, 1g / L KF, and 2g / L K2ZrO3 to water and mix. Some K2ZrO3 precipitates and does not completely dissolve.
[0041] Steps S3-S5): completely consistent with Example 1.
[0042] Performance testing: film thickness 37μm, average hardness 1420HV, neutral salt spray tolerance time 1080h, unmelted zirconium particles and pores appeared in some parts of the film.
[0043] Comparative Example 4 Steps S1-S2): completely consistent with Example 1.
[0044] Step S3): Setting the parameters for the first micro-arc oxidation process: adjust the frequency to 900Hz, and keep the voltage, duty cycle, duration, and temperature the same as in Example 1.
[0045] Steps S4-S5) Zirconia plasma powder spraying and secondary micro-arc oxidation process parameter settings: The secondary oxidation frequency is also adjusted to 900Hz, and the other parameters are the same as in Example 1.
[0046] Performance testing: film thickness 35μm, average hardness 1460HV, neutral salt spray tolerance time 1150h, local discharge spots appeared on the film layer.
[0047] Comparative Example 5 Step S1) Sample pretreatment: Only grinding, degreasing, and alkaline washing are completed, omitting the step of acid washing with 20wt% HNO3 to remove free lithium, and oxidation is carried out directly.
[0048] Steps S2-S5) The remaining processes are completely consistent with those in Example 1.
[0049] Performance testing: film thickness 38μm, average hardness 1610HV, neutral salt spray tolerance time 960h, pinhole defects caused by lithium corrosion appeared on the film surface.
[0050] III. Comparative Analysis Component effect verification: Example 1 vs. Comparative Example 1, after the addition of KF and K2ZrO3, the film hardness increased from 662HV to 1855.7HV, and the salt spray duration increased from 720h to 1900h, proving that the two components are the core of the improvement in hardness and corrosion resistance; Composite process verification: Example 1 vs Comparative Example 2, the "zirconia plasma powder spraying + secondary micro-arc oxidation" step can increase the hardness from 1535HV to 1855.7HV and increase the salt spray duration by 58%, proving that the composite process of in-situ encapsulation of zirconia is the core source of high hardness; Preparation sequence verification: Example 1 vs Comparative Example 3, pre-dissolving K2ZrO3 can avoid precipitation and increase film hardness by 38%, proving that the preparation sequence of the preparation method of the present invention is a necessary condition for film uniformity. Process parameter verification: Example 1 vs Comparative Example 4, deviation from the optimal frequency of 700Hz leads to film formation defects and a 32% decrease in hardness, proving that the parameter range of the preparation method of the present invention is a guarantee of stable performance; Pretreatment verification: Example 1 vs. Comparative Example 5, acid washing to remove free lithium on the surface can avoid pinholes in the film and increase the salt spray duration by 98%, proving that the complete pretreatment of the preparation method of the present invention is the basis for corrosion resistance.
[0051] All embodiments cover all the requirements of the preparation method of the present invention, the parameters are all within the range defined by the preparation method of the present invention, and the performance meets the requirements of hardness ≥1855.7HV and salt spray ≥1900h.
Claims
1. A method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film, characterized in that, Includes the following steps: S1) Sample pretreatment: The aluminum-lithium alloy sample is subjected to mechanical grinding, degreasing, alkaline washing and acid washing in sequence to remove oxide scale, processing marks, oil stains and free lithium ions on the sample surface and activate the alloy substrate surface. S2) Preparation of micro-arc oxidation electrolyte: The electrolyte comprises the following components: Na2SiO3 15-20 g / L, KH2PO4 3-5 g / L, NaOH 1-3 g / L, KF 1-3 g / L, and K2ZrO3 2-4 g / L; The electrolyte is prepared by dissolving 2-4 g / L of K2ZrO3 in pure water, then adding 15-20 g / L of Na2SiO3, 3-5 g / L of KH2PO4, 1-3 g / L of NaOH, and 1-3 g / L of KF in sequence, and stirring thoroughly to obtain a composite electrolyte. S3) First micro-arc oxidation treatment: The pretreated aluminum-lithium alloy sample is placed in the electrolyte, and the micro-arc oxidation reaction is carried out in the mode of first applying positive current and then applying positive and negative current simultaneously. The temperature is controlled throughout the process to complete the initial growth of ceramic film. S4) Surface spraying treatment: After cleaning and drying the sample after one micro-arc oxidation, a zirconium oxide layer is uniformly sprayed onto the surface of the film using a plasma powder spraying process. S5) Secondary micro-arc oxidation treatment: The sample after being sprayed with zirconium oxide is placed again in the electrolyte prepared in step 2), and secondary micro-arc oxidation is performed using a positive and negative energizing mode. The loose zirconium oxide on the surface is wrapped inside the ceramic film layer, and a high-density, high-hardness, and highly corrosion-resistant composite ceramic film layer is generated in situ.
2. The method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film according to claim 1, characterized in that, In step S1), the mechanical polishing involves using sandpaper of different grits to polish from coarse to fine, ultimately using #1000 sandpaper for fine polishing; the degreasing involves using an alkaline degreasing agent and soaking at 50°C for 15 minutes; the alkaline washing involves using a 5% NaOH solution and treating at 60°C for 5 minutes to remove the natural oxide film on the alloy surface; and the acid washing involves using a 20% HNO3 solution and soaking at room temperature for 3 minutes to neutralize alkaline residue, remove free lithium ions from the surface, and activate the substrate surface.
3. The method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film according to claim 1, characterized in that, In step S3), the process parameters for the first micro-arc oxidation are: positive voltage 500V, negative voltage 100V, frequency 700Hz, positive and negative duty cycle 40 / 30, and oxidation time 4h; during the micro-arc oxidation process, the electrolyte temperature is controlled to be constant at 40±2℃ by a circulating cooling system.
4. The method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film according to claim 1, characterized in that, In step S5), the process parameters for the secondary micro-arc oxidation are: positive voltage 510V, negative voltage 120V, frequency 700Hz, positive and negative duty cycle 40 / 30, and oxidation time 4h; the electrolyte temperature is kept constant at 40±2℃ during the secondary micro-arc oxidation process.
5. The method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film according to claim 1, characterized in that, The thickness of the aluminum-lithium alloy micro-arc oxidation ceramic film is 40-45 μm.
6. The method for preparing a high-hardness, corrosion-resistant aluminum-lithium alloy micro-arc oxidation ceramic film according to claim 1, characterized in that, The aluminum-lithium alloy micro-arc oxidation ceramic film has an average hardness of not less than 1820 HV and a neutral salt spray tolerance time of 1900 h.
Citation Information
Patent Citations
Preparation method of titanium alloy high-density micro-arc oxidation film layer
CN113564660A
Aluminum alloy surface treatment method
CN113668032A
